Compensating for loss in equity: the evolution of a remedy - Rickett, Charles; Gardner, Tim (Victoria University of Wellington Law Review, 1994)
Equitable compensation, founded in the inherent jurisdiction of equity, is becoming a more regularly awarded remedy in New Zealand courts. This article examines the features of this remedy first by a comparison between it and the statutory remedy of equitable damages, and secondly by a comparison between it and the common law remedy of compensatory damages in tort law.